The Procedures of Translating Abbreviations in English Medical Texts into Indonesian (e-Journal of Linguistics, 2019)
This study reveals the procedures of translating abbreviations in English medical textsinto Indonesian. It aims at (1) identifying how the abbreviations of English medical terms aretranslated into Indonesian and (2) identifying the phrase of the SL transferred into Indonesian.This study discusses three procedures of translating abbreviations of English medical termswhich are reformulated based on the need of this study, i.e.(1) translating the abbreviation intoabbreviation (borrowing); this procedure showed that the abbreviations of English medical termswere translated into abbreviations, in which borrowing was found (2) translating the abbreviationinto abbreviation (adaptation); this procedure showed that the abbreviations of English medicalterms were translated into abbreviations, in which adaptation was found (3) translating theabbreviation into phrase; this procedure showed that the abbreviation was translated into phrase.The data were taken from the translation of a medical textbook, Oxford Handbook of Midwifery(2006) and its translation into Indonesian Buku Kebidanan Oxford (2010). The results showedthat there were three types of procedures used to translate the abbreviations in this study referredto as translating abbreviation to abbreviation (borrowing), and translating the abbreviation intoabbreviation (adaptation), and translating the abbreviation into phrase.
Keywords: translation; abbreviation; medical terms